An Integrated Pollution Prevention Ecosystem for Small-Scale Production of Raw Coco-nut Jelly in Craft Villages —A Case Study from Mekong Delta, Vietnam - Hai, Le Thanh; Tung, Tra Van; Thanh, Tran Van; Vi, Le Quoc; Thao, Nguyen Thi Phuong; Hieu, Tran Thi; Le, Son; Braunegg, Sibylle; Braunegg, Gerhart; Schnitzer, Hans (Journal of Environmental Accounting and Management, 2026)
Raw coconut jelly is a popular byproduct of the coconut processing industry in the Asia Pacific which can enhance the added economic value for the local families in the rural area. However, the coconut jelly production has resulted in significant environmental impacts, particularly to the aquatic environment due to its heavily polluted wastewater e.g. very high values of COD (up to 120,000 mg/l), of total nitrogen (up to 1,740 mg/l), and of total phosphorus (up to 64 mg/l). The available wastewater treatment technology for such type of wastewater is likely to be not economically efficient due to the small-scale production at craft villages in the developing countries. This study developed and demonstrated an integrated eco-model for small (family) scale production of raw coconut jelly in craft villages which applied Cleaner Production sollutions for pollution prevention on the basis of available conditions at the local family. The system demonstration showed a win-win solution for family with major benefits by reduction of 90% of pollutants (i.e 27 kg COD, 21.4 kg BOD5, approx. 7 kg N, 113 g P and 28 kg SO42−for one production batch), as well as the other benefit by major reduction of 90 % of investment and operating costs of the wastewater treatment plant.